Kelayakan Model Integrasi Usahatani Tebu dengan Usaha Ternak Sapi dalam Menunjang Kesejahetraan Petani Peternak di Kabupaten Kerinci - Firmansyah, Firmansyah; Harahap, Afriani; Dianita, Rahmi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2016)
The research aimed was to assess the technical, institutional, commercial, financial and economic feasibility of integration model of cattle production with sugarcane farming and its effect on the prosperity of farmers in Kayu Aro Barat District, Kerinci Regency. The method used was survey method with Stratified Random Sampling technique. Sampling technque consisted of 2 strata i.e. strata I was sugarcane farmers who integrate to cattle production, and strata II was sugarcane farmers who not integrate to cattle production. Each index used present value from cost and benefit flows that were NPV, Net B/C ratio and IRR. For assessing the effect of integration model of cattle production with sugarcane farming on the prosperity of farmer was used path analysis. The study found that integration cattle production with sugarcane farming in Kayu Aro Barat District, Kerinci Regency was feasible. Technical, commercial, financial and economical aspects were partially affect to farmers’ prosperity in Kayu Aro Barat District, Kerinci Regency. Key words : Integration model, catlle production, sugarcane